Evaluasi Kelengkapan Rambu Lalu Lintas dan Marka Jalan terhadap Tingkat Keselamatan Lalu Lintas di Kota Sorong - Syara, Elfiyusriningsi; Rizal, Muh. Rizal; Kadir, Hamdan; Majid, Hafid Rizaldy; Wasaraka, Julfandy (Syntax Corporation, 2025)
Sorong City is a growing urban center in West Papua Province. This growth is directly proportional to the increasing number of motorized vehicles and the increasing mobility of the population. However, traffic safety is a major concern amidst this development. Traffic signs and road markings have a crucial function in regulating traffic flow and reducing the risk of accidents. However, the completeness, availability, and condition of road signs and markings in Sorong City are not fully understood. Therefore, it is important to evaluate the completeness of road signs and markings and their impact on traffic safety in Sorong City which aims to identify the completeness of traffic signs at various strategic points in Sorong City, examine the condition of road markings including clarity, cleanliness, and their presence on the main roads of Sorong City, measure the impact of the completeness of road signs and markings on the level of traffic accidents in Sorong City and make recommendations for improvements and enhancements to improve traffic safety based on research findings. To achieve the research objectives, the methods that will be used include field surveys, statistical analysis, and GIS mapping. The survey will be conducted systematically in various appropriate locations, including arterial roads, neighborhood roads, and important intersections. Data will be collected using a checklist in the form of aspects such as the existence, clarity, and physical condition of road markings and traffic signs as well as traffic accident data obtained from related parties. The expected output is recommendations for improving traffic infrastructure based on evidence, as well as publication in a journal of at least sinta 2.